An Absolute Mass, Precise Age, and Hints of Planetary Winds for WASP-121A and b from a JWST NIRSpec Phase Curve - David K. Sing; Thomas M. Evans-Soma; Zafar Rustamkulov; Joshua D. Lothringer; Nathan J. Mayne; Kevin C. Schlaufman (The Astronomical Journal)
We have conducted a planetary radial velocity measurement of the ultrahot Jupiter WASP-121b using JWST NIRSpec phase curve data. Our analysis reveals the Doppler shift of the planetary spectral lines across the full orbit, which shifts considerably across the detector (∼10 pixels). Using cross-correlation techniques, we have determined an overall planetary velocity amplitude of K _p = 215.7 ± 1.1 km s ^−1 , which is in good agreement with the expected value. We have also calculated the dynamical mass for both components of the system by treating it as an eclipsing double-line spectroscopic binary, with WASP-121A having a mass of M _⋆ = 1.330 ± 0.019 M _⊙ , while WASP-121b has a mass of M _p = 1.170 ± 0.043 M _Jup . These dynamical measurements are ∼3× more precise than previous estimates and do not rely on any stellar modeling assumptions that have a ∼5% systematic floor mass uncertainty. Additionally, we used stellar evolution modeling constrained with a stellar density and parallax measurement to determine a precise age for the system, found to be 1.11 ± 0.14 Gyr. Finally, we observed potential velocity differences between the two NIRSpec detectors, with NRS1 lower by 5.5 ± 2.2 km s ^−1 . We suggest that differences can arise from day/night asymmetries in the thermal emission, which can lead to a sensitivity bias favoring the illuminated side of the planet, with planetary rotation and winds both acting to lower a measured K _P . The planet’s rotation can account for 1 km s ^−1 of the observed velocity difference, with 4.5 ± 2.2 km s ^−1 potentially attributable to vertical differences in wind speeds.